Cohort profile: COpenhagen ROsacea COhort (COROCO) and COpenhagen MIgraine COhort (COMICO). Issue 8 (20th August 2020) - Wienholtz, Nita Katarina Frifelt; Christensen, Casper Emil; Haugaard, Jeanette Halskou; Zhang, Ditte Georgina; Ashina, Messoud; Thyssen, Jacob Pontoppidan; Egeberg, Alexander
Abstract : Purpose: Migraine has consistently been connected with rosacea. Commonalities in epidemiology, trigger factors and associated neuropeptides support shared aetiology and pathophysiological pathways, though underlying mechanisms remain unclear. We established two cohorts of patients diagnosed with either migraine and/or rosacea. All patients were phenotyped in regard to migraine and rosacea. In this article, we describe the baseline parameters of the cohorts. In the future, we expect that these cohorts will help uncover potential disease overlaps and allow for prolonged follow-up through national Danish health registers. Participants: COpenhagen ROsacea COhort (COROCO) and COpenhagen MIgraine COhort (COMICO) are prospective cohorts based in the Capital region of Denmark. Participants for COROCO were recruited primarily through two tertiary dermatology clinics in Copenhagen, Denmark and patients for COMICO were recruited through a tertiary neurology clinic in Copenhagen, Denmark. Findings to date: COROCO: 67.7% women (median age 51 years (interquartile range (IQR) 43.0–61.0)). Family history of migraine: 44.3%. Family history of rosacea: 45%. There were 13% who currently smoked, and 36.6% were former smokers. Regular intake of alcohol was present in 79.3% (median 4 items/week (IQR 1.0–9.0)). Median body mass index (BMI): 25.7 (IQR 23.1–29.0). Median Dermatology Life Quality Index (DLQI): 2 (IQR 1–5). COMICO: 88.5% women (median age 41 years (IQR 29.5–51.0)). Family history of migraine: 73.4%. Family history of rosacea: 18.4%. There were 17.1% who currently smoked, and 26.0% former smokers. Regular intake of alcohol was present in 62.2% (median intake: 2 item/week (IQR 1.0–3.0)). Median BMI was 24.6 (IQR 21.5–28.2). Median DLQI was 1 (IQR 0–2). Future plans: COROCO and COMICO serve as strong data sources that will be used for future studies on rosacea and migraine with focus on risk factors, occurrence, treatment, natural history, complications, comorbidities and prognosis. Trial registration number: ClinicalTrials.gov Registry (NCT03872050 ).